Influence of dry, extruded-expelled soybean meal from different manufacturers on growth performance of nursery pigs - Woodworth, J.C.; Steidinger, M.U.; DeRouchey, Joel M.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 150 pigs (initially 22 lb; 42 d of age) was used to determine the influence of dry, extruded-expelled soybean meal from three different manufacturers on growth performance of pigs. No differences were observed for ADG, ADFI, or F/G between any of the sources. All three sources resulted in performance similar to that with a cornsoybean meal diet with added fat. These results confirm the accuracy of the energy values published in the 1998 Swine Day Report for dry, extruded-expelled soybean meal.
Keywords: Swine; Nursery pigs; Growth; Soybean meal; Processing